2016
DOI: 10.18632/oncotarget.14169
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of nano-PTX to the brain tumor-associated macrophages

Abstract: Nanoparticles containing mixed lipid monolayer shell, biodegradable polymer core and rabies virus glycoprotein (RVG) peptide as brain targeting ligand, were developed for brain targeted delivery of paclitaxel (PTX) to treat malignant glioma. RVG conjugated PTX loaded NPs (RVG-PTX-NPs) had the desirable size (~140 nm), narrow size distribution and spherical shape. RVG-PTX-NPs showed poor uptake by neurons and selective targeting to the brain tumor associated macrophages (TAMs) with controlled release and tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…43,49,105 On the other hand, RVG is a neurotropic virus peptide that binds to the nicotinic acetylcholine receptors and facilitates nanoparticle delivery to the brain and brain tumors. 47,[53][54][55]60 When evaluating nanoparticles' capacity to internalize GBM cells and inhibit the expression of miR-92b in vitro, we observed that SNAs, SNA-Liposomes, SNA-Liposome-ApoE, and SNA-Liposome-RVG had similar delivery efficiencies than the lipofectamine used as a positive control. Our in vivo results confirmed our hypothesis that ApoE and RVG peptides would enable RNAi systemic delivery into brain tumor cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…43,49,105 On the other hand, RVG is a neurotropic virus peptide that binds to the nicotinic acetylcholine receptors and facilitates nanoparticle delivery to the brain and brain tumors. 47,[53][54][55]60 When evaluating nanoparticles' capacity to internalize GBM cells and inhibit the expression of miR-92b in vitro, we observed that SNAs, SNA-Liposomes, SNA-Liposome-ApoE, and SNA-Liposome-RVG had similar delivery efficiencies than the lipofectamine used as a positive control. Our in vivo results confirmed our hypothesis that ApoE and RVG peptides would enable RNAi systemic delivery into brain tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, both peptides have proven to facilitate the delivery of different nanoparticles into GBM cells in vitro and in vivo. 54,[56][57][58][59][60] In this study, we synthesized nanoparticles capable of delivering OMIs inside GBM cells in vitro and in vivo. We generated SNAs by chemically functionalizing OMIs to AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…They showed the decreased tumor size and increased survival of mice treated with these NPs. Zou et al investigated the effectiveness of paclitaxel-loaded PLGA NPs in targeting brain tumor-associated macrophages [124]. Their results demonstrated the beneficial effects of these NPs in the treatment of gliomas.…”
Section: Plgamentioning
confidence: 99%
“…Receptor-mediated transcytosis offers a highly specific transport mechanism through the binding of conjugated ligands to specific receptors. With respect to CNS macrophage targeting, lactoferrin [222], transferrin receptor binding peptide [224], rabies virus glycoprotein [225], and mannose [197] are among those that have been explored.…”
Section: Optimising Delivery and Np/mp Uptake In Macrophagesmentioning
confidence: 99%